Analysis of the Book Ilmu Nahwu untuk Pemula: A Perspective from Mackey and Thu’aimah - Boby Bagas Purnama; Muhajir; Noor Auliya Huda; Siska Nanda Safitri (South Sulawesi Education Development (SSED), 2025)
Nahwu books are essential for understanding Arabic sentence structures, but choosing the wrong one can hinder learning. This study evaluates the book Ilmu Nahwu untuk Pemula based on Mackey’s and Thu’aimah’s theories to assess its quality and effectiveness. Using a qualitative library research approach, the study follows Mestika Zed’s procedures: (1) identifying research variables in the book, (2) searching for supporting information, (3) selecting relevant materials, and (4) analyzing and categorizing data. The analysis reveals that the book meets most of Mackey’s criteria, including selection, gradation, presentation, and repetition, but lacks ostensive and pictorial procedures. According to Thu’aimah, the book offers strong grammatical explanations but less focus on cultural aspects and integrating other language skills. Overall, it is effective for beginner nahwu learners, but improvements in visual elements and cultural integration are needed for a more holistic learning experience.